An Analysis of the River Fishermen Profit-Sharing System: Based on the Perspective of Fiqh Muamalah in Kampung Rakyat District, South Labuhan Batu Regency - Masleni Nasution; Tuti Anggraini; Waizul Qarni (Al-Hiwalah: Journal of Sharia Economic Law, 2026)
Abstract: The river fishing sector serves as a primary economic pillar for the community in Kampung Rakyat District, South Labuhanbatu Regency; however, profit-sharing practices between boat owners and hired fishermen (crew members) face structural challenges regarding the lack of clarity and inequity in profit distribution. This study aims to examine the profit-sharing mechanisms employed by these river fishermen and analyze their alignment with the principles of fiqh muamalah (Islamic commercial law) and maqashid sharia (the objectives of Sharia). A descriptive qualitative approach was adopted, utilizing data collected through in-depth interviews, field observations, and documentation involving six crew members and three boat owners as key informants, with source triangulation employed to ensure data validity. The findings reveal that the prevailing profit-sharing system relies on verbal agreements rather than clear written contracts, characterized by limited transparency regarding operational cost calculations, fish pricing and sales data, and the determination of profit-sharing ratios between capital owners and workers. From the perspective of fiqh muamalah, these practices contain elements of gharar (uncertainty) and fail to fully satisfy contractual requirements concerning the clarity of the object, fairness, and the mutual consent of the parties involved. Furthermore, maqashid sharia values specifically hifdz al-mal (preservation of wealth) and hifdz al-nafs (preservation of life/well-being) are not optimally realized due to inadequate protection of the crew members' economic rights and livelihood sustainability. These findings underscore the need to strengthen contract governance within the economic practices of coastal and riverine communities. The study recommends the implementation of formal written contracts, mechanisms for transparency regarding costs and sales proceeds, and institutional support from local governments and Sharia financial institutions to foster profit-sharing practices that are fairer, more transparent, and compliant with Sharia principles.